Sieving process selects sugarcane bagasse with lower recalcitrance to xylan solubilization - Alves, Rosângela C [UNESP]; Melati, Ranieri B [UNESP]; Casagrande, Giovanna MS [UNESP]; Contiero, Jonas [UNESP]; Pagnocca, Fernando C [UNESP]; Brienzo, Michel [UNESP] (Wiley, 2020)
BACKGROUND: Sugarcane bagasse is a heterogeneous and organized material that needs a pretreatment to access the polysaccharides (cellulose and xylan). The particle size of a non-milled bagasse can influence the xylan and xylose solubilization, as well as the enzymatic hydrolysis of the pretreated material. Using bagasse selected on 16-, 30-, 40- and 50-mesh sieves: xylan solubilization was performed with hydrogen peroxide; xylose was solubilized with diluted sulfuric acid; and enzymatic hydrolysis was conducted for glucose yield evaluation. RESULTS: The xylose solubilized by acid pretreatment resulted in a maximum of 6.59 g L−1 with no influence of particle size. The solubilized xylan showed linear correlation with a variation of 36.18% (16-mesh bagasse) to 71.43% (<50-mesh bagasse). Pretreated material submitted to enzymatic hydrolysis revealed that particle size influenced the pretreatment, increasing the glucose yield. CONCLUSIONS: The results showed that non-milled sugarcane bagasse particle size selection positively influenced the solubilization of xylan, improving the enzymatic hydrolysis of the pretreated material. © 2020 Society of Chemical Industry (SCI).
Keywords: acid extraction; alkaline extraction; granulometry; hemicellulose; lignocellulosic biomass